Human Immunodeficiency Virus-associated Neurocognitive Impairment in Diverse Resource-limited Settings. (13th September 2018) - Robertson, Kevin R; Jiang, Hongyu; Kumwenda, Johnstone; Supparatpinyo, Khuanchai; Marra, Christina M; Berzins, Baiba; Hakim, James; Sacktor, Ned; Campbell, Thomas B; Schouten, Jeffrey; Mollan, Katie; Tripathy, Srikanth; et al.
Abstract: Background: Neurocognitive impairment remains a common complication of human immunodeficiency virus (HIV) despite effective antiretroviral therapy (ART). We previously reported improved neurocognitive functioning with ART initiation in 7 resource-limited countries for HIV+ participants from the AIDS Clinical Trials Group (ACTG) 5199 International Neurological Study (INS). Here, we apply normative data from the International Neurocognitive Normative Study (INNS) to INS to provide previously unknown rates of neurocognitive impairment. Methods: The A5199 INS assessed neurocognitive and neurological performance within a randomized clinical trial with 3 arms containing World Health Organization first-line recommended ART regimens (ACTG 5175; PEARLS). The ACTG 5271 INNS collected normative comparison data on 2400 high-risk HIV-negative participants from 10 voluntary counseling and testing sites aligned with INS. Normative comparison data were used to create impairment ratings for HIV+ participants in INS; associations were estimated using generalized estimating equations. Results: Among 860 HIV+ adults enrolled in ACTG 5199, 55% had no neurocognitive impairment at baseline. Mild neurocognitive impairment was found in 25%, moderate in 17%, and severe in 3% of participants. With the initiation of ART, the estimated odds of impairment were reduced 12% (95% confidence interval, 9%, 14%) for every 24 weeks ( P < .0001) on ART. Mild impairment dropped slightly and then remained at about 18% out to week 168. Conclusions: Almost half of HIV+ participants had neurocognitive impairment at baseline before ART, based on local norms. With ART initiation, there were significant overall reductions in neurocognitive impairment over time, especially in those with moderate and severe impairments. Clinical Trials Registration: NCT00096824. Abstract : AIDS Clinical Trials Group A5199 compared the neurological and neuropsychological results in 860 human immunodeficiency virus-positive participants from seven resource limited countries randomized on 3 antiretroviral regimens. Participants showed improved neurocognitive function following antiretroviral therapy initiation compared to normative data.